Hypolipidemic and anti‐atherogenic activities of crude polysaccharides from abalone viscera. Issue 5 (20th April 2020) - Liu, Binxiong; Jia, Zhen; Li, Changcheng; Chen, Jinquan; Fang, Ting
Abstract: This study was performed to evaluate the hypolipidemic and anti‐atherogenic activities of the crude polysaccharides extracted from abalone viscera (AVCP). The major functional groups of purified polysaccharides were analyzed by infrared spectroscopy (IR). Male Kunming mice (SPF) were divided into six groups and were treated with normal diet or high‐fat diet with AVCP or Xuezhikang (hypotensive drug) for 5 weeks. Physicochemnical analysis of AVCP showed the presence of 60.4% polysaccharides, 17.9% protein, 6.0% fat and 10.9% moisture. The IR analysis of AVP showed the presence of functional groups of sugar moiety and sulfate groups. The results demonstrated that AVCP not only led to significant reduction of total cholesterol (TC), triglycerides (TG), low‐density lipoprotein cholesterol (LDL‐C), and increase of high‐density lipoprotein cholesterol (HDL‐C) in plasma, but also to significant increments of malondialdehyde (MDA) and superoxide dismutase (SOD) activities. However, AVCP played no role in mice weight. Furthermore, the results of the photomicrograph of liver tissue showed that AVCP reduced lipid droplets and prevented the disordered structure of the liver. The results suggested that AVCP exhibited significantly hypolipidemic and anti‐atherogenic activities. Abstract : The antihyperlipidemic and antiatherosclerotic activities of crude polysaccharide from abalone viscera were investigated by rat experiment. The results showed it not only significantly reduce plasma total cholesterol (TC), triglyceride (TG), low‐density lipoprotein cholesterol (ldl‐c), and high‐density lipoprotein cholesterol (hdl‐c), but also significantly improve the activity of malondialdehyde (MDA) and superoxide dismutase (SOD).